Has global agricultural trade been resilient under coronavirus (COVID-19)? Findings from an econometric assessment of 2020. (February 2022) - Arita, Shawn; Grant, Jason; Sydow, Sharon; Beckman, Jayson
Highlights: Agricultural trade has often been described as "resilient" to the COVID-19 pandemic. The COVID-19 pandemic reduced agricultural trade by 5 to 10 percent in aggregate. Agricultural trade effects are 2–3 times smaller than non-agricultural trade impacts. Most non-food items and higher value agri-food products were more severely impacted by the pandemic. The pandemics effect also affected the extensive margin of product throughput per port. Abstract: Global agricultural trade, which increased at the end of 2020, has been described as "resilient" to the impacts of the COVID-19 coronavirus pandemic; however, the size and channels of its quantitative impacts are not clear. Using a reduced-form, gravity-based econometric model for monthly trade, we estimate the effects of COVID-19 incidence rates, policy restrictions imposed by governments to curb the outbreak, and the de facto reduction in human mobility/lockdown effect on global agricultural trade through the end of 2020. We find that while agricultural trade remained quite stable through the pandemic, the sector as a whole did not go unscathed. First, we estimate that COVID-19 reduced agricultural trade by the approximate range of 5 to 10 percent at the aggregate sector level; a quantified impact two to three times smaller in magnitude than our estimated impact on trade occurring in the non-agricultural sector. Second, we find sharp differences across individual commodities. In particular, we find that non-food items (hides and skins, ethanol, cotton, and other commodities), meat products including seafood, and higher value agri-food products were most severely impacted by the pandemic; however, the COVID-19 trade effect for the majority of food and bulk agricultural commodity sectors were found to be insignificant, or in a few cases, positive. Finally, we also examine the effects across low vs high income countries, the changing dynamics of the pandemic's effect on trade flows, and the effects along the extensive product margins of trade.